Formulasi Hukum Hak Terkait Untuk Pelaku Seni Pertunjukan Teater Di Yogyakarta - Ahmad Muhsin (JIPRO: Journal of Intellectual Property, 2020)
The main problem in this research is to examine the related rights for actors in theater performances as regulated in Law No. 28 of 2014 concerning copyright, as for the formulations of the problems presented, namely: First, is the formulation of Related Rights in the Copyright Law No. 28 of 2014 in accordance with the views of theater actors in Yogyakarta? Second, How is the formulation of Related Rights in the Copyright Law No. 28 of 2014 according to the future view of theater actors in Yogyakarta? This study uses the normative-empirical method, while the conclusions of this research are: First, that the related rights law rules in the Copyright Law No. 28 of 2014 is complete, Second. The views of theater performers regarding the formulation of rights law related to the future need to be regulated in more detail regarding the standardization of forms of cooperation in the creative process and forming a collective management institution that focuses on protecting theater arts.